THE POLITICS OF PUBLIC PIETY IN CONTEMPORARY MUSLIM SOCIETIES: RELIGIOUS SYMBOLIC REPRESENTATIONS, SOCIAL MEDIA, AND THE PRODUCTION OF MORAL LEGITIMACY - Zaid Al-Bustami (NIHAYAH: Journal of Islamic Studies, 2026)
The digitalization of religious life has transformed piety from a private spiritual affair into a performative public politics. This study explores the politics of public piety in contemporary Muslim society by analyzing how religious symbols are represented on social media to produce moral legitimacy. Using a qualitative method with a digital discourse analysis approach, this research examines religious content, digital symbols, and moral narratives across platforms such as Instagram and TikTok. The findings reveal that public piety has become a form of symbolic capital, where the curation of visual aesthetics, sartorial attributes, and lifestyle-based religious narratives are strategically utilized to construct an image of moral authority. This study identifies that moral legitimacy is increasingly produced through digital validation such as engagement metrics rather than traditional institutional certification. This shift signifies a democratization of authority that paradoxically creates new social stratifications based on religious lifestyle aesthetics. Theoretically, this research reinforces the concepts of symbolic power and discursive regimes in the digital religious sphere. The implications of this study suggest that the performativity of piety on social media shifts the focus from substantive spiritual transformation to image-based representation, leading to a fragmentation of traditional religious structures. Consequently, this research emphasizes the need for a more critical understanding of how digital platforms reshape authentic religious authority and social power relations in modern Muslim communities.